Evaluation of Anti-Cancer Activity of Momordica dioica using MTT and DAPI Assays (Asian Journal of Pharmaceutics (AJP), 2025)
Aim: The aim of this study was to evaluate the anti-cancer potential of methanolic extracts from the stem-leaf,root, and callus of Momordica dioica against two cancer cell lines: Michigan Cancer Foundation-7 (MCF-7)(human breast cancer) and A549 (lung cancer). Materials and Methods: The evaluation was conductedusing the 3-(4,5-Dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay and 4′,6-Diamidino-2-phenylindole (DAPI) staining method, which are reliable and widely used techniques in cancer research. TheMTT assay, a sensitive and quantitative colorimetric method, assessed cell viability, proliferation, and metabolicactivity. Results and Discussion: The results revealed that methanolic stem-leaf and callus extracts significantlyinhibited the growth of MCF-7 cells at IC50 concentrations, indicating their effectiveness in targeting breastcancer cells. DAPI staining, a fluorescence-based method used to detect DNA fragmentation and apoptosis, wasapplied to the A549 lung cancer cell line. The findings demonstrated a dose-dependent induction of apoptosisin A549 cells treated with the extracts, suggesting their potential role in activating apoptotic pathways in lungcancer cells. Overall, these results highlight the promising anti-cancer properties of M. dioica methanolicextracts. Conclusion: The plant extract can inhibit cancer cell growth and induce apoptosis, underscoring theirpotential as natural therapeutic agents. This study provides a foundation for further research aimed at isolatingand characterizing the active compounds responsible for these effects, which could lead to the development ofnovel and effective anti-cancer drugs.